Tulen: Mah Meri cultural centre / Mohamad Ridhwan Mohamad Zamri ... [et al.] - Mohamad Zamri, Mohamad Ridhwan; Aris White, Nabilah; Za'abar, Zarina; Hasri, Hazirah (College of Built Environment, 2023)
Malaysia is one of the countries that is not exempt from being hit hard by the Covid -19 pandemic.